PRACTICING THE SUNNAH AND HADITH IN EVERYDAY LIFE: A LIVING HADITH STUDY OF THE IMPLEMENTATION OF SUNNAH VALUES IN MUSLIM COMMUNITIES - Zulheddi Zulheddi; Afifatul Hizmi; Annida Azhari Ritonga; Mentari Asshiddiqie (Journal Analytica Islamica, 2026)
The Sunnah and Hadith are the second source of Islamic teachings after the Quran, and play a crucial role in shaping individual behavior and the social life of Muslim communities. This study aims to analyze the practice of the Sunnah and Hadith in daily life through a living hadith approach. The method used is qualitative research with a library research approach, utilizing various scientific literature, journals, books, and the latest research findings. The results show that the practice of the Sunnah in daily life remains an important part of Muslim communities, both in the form of worship, morals, and social interactions. The implementation of the Sunnah can shape religious character, increase social solidarity, and strengthen Islamic identity amidst the challenges of modernization. However, technological developments and changes in modern lifestyles also influence the level of understanding and practice of the Sunnah. Therefore, ongoing educational efforts are needed to ensure that the values of the Sunnah remain relevant and applicable in contemporary life.